DINAMIKA PENGUATAN FUNGSI PUTUSAN MAHKAMAH AGUNG SEBAGAI LEMBAGA PERADILAN DI INDONESIA - Holijah, Holijah (Universitas Islam Negeri Raden Fatah Palembang, 2014)
Abstract: The constitution guarantees the independence of judicial power is for power. The Supreme Court is one of the legal institutions that hold judicial functions and other functions of which are functions of supervision in the form of repressive surveillance authority. Need an optimal effort in the various components of the legal system as well as increasing awareness of the law in each of the affected communities to strengthen the Supreme Court. Dynamics strengthening the Supreme Court as a law enforcement and justice agencies in Indonesia in an attempt to guarantee the implementation of an independent judiciary, free from the influence of other powers to organize courts to uphold law and justice.ملخص: يضمن الدستور استقلال السلطة القضائية عن السلطة. المحكمة العليا هي واحدة من المؤسسات القانونية التي تحمل الوظائف القضائية وغيرها من المهام منها مهام الإشراف في شكل من أشكال السلطة القمعية المراقبة. تحتاج إلى جهد الأمثل في مختلف مكونات النظام القانوني وكذلك زيادة الوعي للقانون في كل من المجتمعات المتضررة لتعزيز المحكمة العليا. ديناميات تعزيز المحكمة العليا باعتبارها إنفاذ القانون وأجهزة العدالة في إندونيسيا في محاولة لضمان تنفيذ نظام قضائي مستقل، وخالية من تأثير القوى الأخرى لتنظيم المحاكم لدعم القانون والعدالة.Kata kunci: konstitusi, mahakamah agung, kekuasaan hakim